Amorphous NiP supported on rGO for superior hydrogen generation from hydrolysis of ammonia borane. (18th May 2017) - Du, Xiaoqiong; Yang, Chenlu; Zeng, Xiang; Wu, Tong; Zhou, Yinghui; Cai, Ping; Cheng, Gongzhen; Luo, Wei
Abstract: Transition metal phosphide based amorphous NiP/rGO hybrids have been successfully synthesized through a facile one-pot co-reduction method. The prepared NiP/rGO hybrids are characterized by powder X-ray diffraction (XRD), inductively coupled plasma-atomic emission spectroscopy (ICP-AES), X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM) and energy dispersive X-ray detector (EDX) techniques. Compared with Ni/rGO, the resulted Ni91 P9 /rGO hybrid exhibits superior catalytic activity toward hydrogen generation from hydrolysis of ammonia borane (NH3 BH3 ), with turnover frequency (TOF) value of 13.3 min −1 . The activation energy (Ea) of Ni91 P9 /rGO for this reaction is calculated to be 34.7 kJ mol −1, which is much lower than those of the other reported catalysts. This superior catalytic performance may be due to the good dispersibility of Ni91 P9 nanoparticles and the synergistic electronic interactions between nickel and phosphorus. Highlights: Facile one-pot wet-chemical approach to prepare P-doped Ni nanoparticles. Transition metal phosphide is used as efficient catalysts for NH3 BH3 hydrolysis. NiP/rGO exhibits superior catalytic activity and stability toward NH3 BH3 hydrolysis.